Analisis Dampak Daging Sapi Impor terhadap Keberlangsungan Usaha Pedagang Lokal Pasar Ibuh Menurut Ekonomi Islam - Divo; Awaluddin; M Imamuddin; Muhammad Rais (LPPM STAI Muhammadiyah Probolinggo, 2025)
This study aims to analyze the impact of the availability of imported beef on sales and business continuity of local traders in Ibuh traditional market, Payakumbuh City, as well as evaluate the price competition from the point of view of Islamic economics. The method used in this study is descriptive qualitative approach, with data collection through interviews with 10 informants, field observation, and literature studies. The findings showed that the availability of imported beef resulted in a decrease in sales of local traders by 34.4%. The main factors driving this are lower prices for imported meat, longer shelf life and wider distribution. Local merchants responded with adaptive strategies, such as improving services and providing discounts.In addition, in the perspective of Islamic economics according to Ibn Taymiyah, this condition is contrary to the principle of justice that requires prices to be formed fairly without exploitation. This inequality requires government intervention through the role of hisbah, such as subsidizing local meat prices or restricting imports,protecting small traders and creating fair market competition.